(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Treatment of the environment with the perception of it merely being a resource to further the human domain on the planet has come under scrutiny after seeing its impact in the form of environmental imbalance and climate change. Countering to it the field of Environmental philosophy deals with the unexamined values, assumptions and different ideologies existing in humanity towards nature and tries to elicit an effective response pertaining to a nature centric sustainable framework. The research presented here, with the help of a questionnaire and hence the data received tries to make sense of the societal perspective, attitude and the understanding of sustainability. It tries to decipher the differences in the idea of “Sustainable Development” which is, eitherAnthropocentric, where nature is barely a means for humanity to utilise as deemed judicious by the parameter self-designated by humans or an idea of ecocentrism, which goes beyond the consideration of individuals and extends moral consideration to the ecosystems as a whole. Ecocentrism emphasizes the interconnectedness and interdependence of all living and non-living components of ecosystem, recognizing their inherent value and the need to preserve ecological integrity. So that just and pertinent value should be given to all non-human components of the environment.